2023
DOI: 10.1371/journal.pone.0290245
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sex expression profiles and the cantharidin biosynthesis genes in two blister beetles

Yuan-Ming Wu,
Jia-Ran Li,
Jiang Li
et al.

Abstract: Cantharidin (CTD) is a well-established defensive toxin synthesized by blister beetles, displaying both therapeutic potential and toxicity. Among these beetles, Hycleus cichorii and Hycleus phaleratus are the two most commercially significant species due to their capacity to produce CTD in males. In this investigation, we conducted a gene expression profiling analysis of male and female individuals of these two species, utilizing the Illumina Hiseq4000 platform. We identified 7,983 expressed genes, including 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated that FOHSDR and JHEH, which are related to CTD synthesis in blister beetles, ,, and serve as downstream factors of FPPS in the juvenile hormone III (JHIII) pathway (Figure F, and SI, Figure S3). , We therefore also examined the expression level of these two genes in dsFPPS treated beetles.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that FOHSDR and JHEH, which are related to CTD synthesis in blister beetles, ,, and serve as downstream factors of FPPS in the juvenile hormone III (JHIII) pathway (Figure F, and SI, Figure S3). , We therefore also examined the expression level of these two genes in dsFPPS treated beetles.…”
Section: Resultsmentioning
confidence: 99%